Exploring the psycho-social needs of families of COVID-19 victims and their reactions to health protocol adherence after bereavement: a qualitative study - Seyed Fahim Irandoost; Ahmad Ahmadi; Samira Esprooz; Mandana Saki; Murat Yıldırım; Rana Hosseini; Javad Yoosefi Lebni (BMC Psychology)
Abstract Background The onset of COVID-19 and its resulting deaths bring family members to face vast challenges and new needs for them. The type of reaction of family members of the victims after the catastrophe of the death of loved ones due to COVID-19 is different. Therefore, the current research was aimed at addressing the psycho-social needs of the families of COVID-19 victims and their reaction to compliance with post-death health protocols. Methods The present study was conducted using a qualitative approach and a method of conventional content analysis among 30 members of the families of the victims of COVID-19 in the provinces of Lorestan and Tehran in Iran. Participants were reached, and data were collected both face-to-face (23 cases) and online (7 cases) through purposive sampling and snowball sampling as well as semi-structured interviews. Data management was carried out using the MAXQDA-2018 software and its analysis with the Graneheim and Lundman approach method. Guba and Lincoln’s criteria were also followed to improve the quality of results. Results The findings showed two main categories and nine sub-categories, including (1) needs (financial needs, psychological needs, social needs, educational needs, and spiritual needs) and (2) survivors’ reaction to health protocol compliance (carelessness in following protocols, extreme strictness and obsession with following health protocols, encouraging and persuading people to comply with health protocols, revenge from society). Conclusion The findings of the study showed that families of COVID-19 victims face many challenges after a patient’s death, which leads to the creation of new needs in them as well as the reaction of families after the death of one member, which in some cases can be dangerous to society and requires attention. Hence, it is necessary to do both support and intervention and policy.